2005
DOI: 10.1080/0968759042000283638
|View full text |Cite
|
Sign up to set email alerts
|

A common open space or a digital divide? A social model perspective on the online disability community in China

Abstract: This paper explores the use and impact of the Internet by disabled people in China, informed by the social model of disability. Based on survey data from 122 disabled individuals across 25 provinces in China, study findings suggest that there is an emerging digital divide in the use of Internet amongst the disability community in China. Internet users in our study do not appear to be representative of most disabled people in China. For the minority of disabled people who do have access to the Internet, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 21 publications
3
68
0
Order By: Relevance
“…A survey study in China indicated that a minority of people with disability have access to the internet; this represents a digital divide (Guo, Bricout and Huang, 2005). People with disability who have access experience a significant increase in frequency of social interactions and reduction of existing barriers in the physical and social environment.…”
Section: Theme 1: Access To Technologymentioning
confidence: 99%
“…A survey study in China indicated that a minority of people with disability have access to the internet; this represents a digital divide (Guo, Bricout and Huang, 2005). People with disability who have access experience a significant increase in frequency of social interactions and reduction of existing barriers in the physical and social environment.…”
Section: Theme 1: Access To Technologymentioning
confidence: 99%
“…Though they have led to great insights, many existing studies draw from small and/or nonrepresentative samples (e.g., Bradley and Poppen 2003;Finn 1999;Grimaldi and Goette 1999;Guo, Bricout and Huang 2005;Seymour and Lupton 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both WeChat and QQ have voice message functionality, which could meet the special needs of people with disabilities. Guo, Bricout, and Huang (2005) indicated that the Internet can effectively reduce existing social barriers in social and physical environment for people with disabilities. Research has shown that social media platforms such as WeChat, Twitter, and Facebook are developing rapidly in the contexts of interpersonal communication, news and information dissemination, education, and other fields (Chen & Bryer, 2012;Gikas & Grant, 2013).…”
Section: Discussionmentioning
confidence: 99%